RESEARCH OF THE FRICTIONAL PROPERTIES OF WALNUT BOUGH BARK - Крупич, Р. О. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The method and results of research of the coefficient and angle of the friction between the trapping pillows of the fruit shaker and the bark of the skeletal branches (boughs) of walnut are presented. The research was carried out with the aim of determining the constructive parameters of the fork capture of the hand shaker of nuts. During experiments the academician V.O. Zheligovsky device was used. The specimens with a diameter of 30, 50, 60, 70, 80.90 and 120 mm were taken from the skeletal branches of the walnut of the first and second orders. The samples of the fruit branches were fastened in the carriage of the device. The coefficient and angle of friction between the rubber lining and the bark of the branches were determined both transversely and along the fibers. The study of the frictional properties of the bark of the branches confirms that the coefficient and angle of friction depend deeply on the roughness of the contact surfaces of the branches and pillows of capture, as well as the relative displacement of these surfaces - across or along the fibers. For branches with a diameter of 30-90 mm, the coefficient and angle of friction across the fibers varies within the limits of 0.476-0.484 and 25.45-25.83° accordingly. With the diameter of the 120 mm branches, these figures increase and make up: the coefficient of friction is 0.532, the angle of friction is 28 °. Friction indices along the fibers of the crust of branches with a diameter of 30 - 90 mm are: coefficient of friction - 0,501-0,515; Friction angle - 26,61-27,25 °, and for branches with a diameter of 120 mm, the coefficient of friction is 0,562 and the angle of friction is 29,34 °. The angle of the pillow slope of the fork capture should be 40°